Clinical trials with new oral anticoagulants - Harenberg, J.; Weiss, C. (Hämostaseologie, 2013)
To compare the efficacy and safety of the new oral anticoagulants (NOAC), ideally head-to-head clinical trials should be performed. Given the expense of such an undertaking, it is highly unlikely that such a comparison would be performed. Therefore, there is a need for an unbiased comparative assessment of the benefits and risks of the NOACs, based on the available trial data. Indirect or mixed treatment comparisons may be an useful tool to overcome these limitations also known as network meta-analysis (NMA).The aim of this paper is to give an overview on published NMAs for dabigatran, rivaroxaban and apixaban, each assessed against warfarin in patients with atrial fibrillation, and against enoxaparin in patients undergoing total knee and total hip replacement surgery, in order to obtain insights into the comparability of the adopted methodological techniques.
Keywords: Oral anticoagulants; apixaban; dabigatran; rivaroxaban; atrial fibrillation; total knee replacement; total hip replacement; prophylaxis of thromboembolism